Genome-Wide Identification of Long Non-coding RNAs Responsive to Lasiodiplodia theobromae Infection in Grapevine. (April 2019) - Xing, Qikai; Zhang, Wei; Liu, Mei; Li, Lingxian; Li, Xinghong; Yan, Jiye
Long non-coding RNAs (lncRNAs) refer to a class of RNA molecules that are longer than 200 nucleotides and do not encode proteins. Numerous lncRNAs have recently emerged as important regulators of many biological processes in animals and plants, including responses to environmental stress and pathogens. Botryosphaeria dieback is one of the more severe grapevine trunk diseases worldwide. However, how lncRNAs function during Botryosphaeriaceae infection is largely unknown. We performed high-throughput RNA-sequencing (RNA-seq) of susceptible and more tolerant grapevine cultivars infected with Lasiodiplodia theobromae . Overall, we predicted 1826 novel candidate lncRNAs, including long intergenic non-coding RNAs (lincRNAs) and natural antisense transcripts (lncNATs). The data reveal the functions of a set of lncRNAs that were differentially expressed between the resistant cultivar Merlot and the susceptible cultivar Cabernet Franc. Several lncRNAs were predicted to be precursors for grape microRNAs involved in the L theobromae infection. These results provide new insight into the lncRNAs of grapevine that are involved in the response to L theobromae infection.